SEMANTIC DISTINCTIVENESS OF THE ENGLISH DEFINITE AND INDEFINITE ARTICLES AND WAYS OF TRANSLATION - Kobilova N.S, Hasanova M.A (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the semantic distinctiveness of the English definite (the) and indefinite (a/an) articles, analyzing their nuanced roles in communication and the challenges they pose in translation. The study highlights how these articles contribute to specificity, genericity, and definiteness in English syntax and discourse. The definite article is examined as a marker of familiarity, shared knowledge, or uniqueness, while the indefinite article signals new information, generality, or non-specificity. Drawing comparisons with languages that lack equivalent article systems or use alternative structures, the article delves into the complexities of translating these markers into target languages. Various strategies, such as contextual adaptation, structural substitution, and lexical additions, are discussed to address the challenges translators face when conveying the semantic roles of English articles. By examining examples from bilingual texts, the study underscores the importance of cultural and linguistic context in preserving the meaning and function of articles during translation. This research contributes to a deeper understanding of the interplay between grammatical systems and translation, offering practical insights for linguists, translators, and language learners.